The use of heart rate for monitoring the acclimatization status to high altitude training in cross-country skiers - Takeda, M.; Kato, H.; Mimura, T.; Shimamoto, H.; Endoh, H.; Radak, Z. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Because of the fact that there are benefits and risks in high altitude training (Wilber, 2003), it is reasonable to have an index for monitoring physical condition and acclimatization status in high altitude training. In this study, we have evaluated physiological meanings of resting heart rate for monitoring the physical condition and acclimatization status during 2 weeks of high altitude training in crosscountry skiers. Methods: Collegiate cross-country skiers (8 males, 6 females, 20 ± 1.0 yrs.) lived 1 day at sea level and lived and trained for 14 days at 2,200 m. Just soon after getting up, the following items were measured in every 2 days, i.e., heart rate (HR) during orthostatic test, hemoglobin concentration (Hb), and HR, blood lactate concentration (La), and ratings of perceived exertion (RPE) during 3 minutes of submaximal cycling test at the intensity of 75% of maximal HR of each subject and 3 minutes of recovery. Erythropoietin (EPO), ferritin, red blood cell (RBC), hematocrit (Hct) were measured at sea level and day 2 and 15 stayed at high altitude. One way repeated measure of variance and correlation analyses were used for the statistical evaluations. Results: Supine and standing HR significantly increased at day 2 (vs sea level) and, after that, gradually decreased during acclimatization process of 2 weeks of high altitude training. Supine HR was significantly decreased at day 12 (vs. day 2). Likewise, salivary cortisol was significantly increased at day 2 (vs sea level) and, after that, significantly decreased at day 14 (vs day 2 and 8). EPO was significantly increased after 48 h at 2,200 m (vs. before altitude training) and significantly returned to the same level with sea level at day 14. Hb was significantly increased day14 (vs. con, day 2). No significant changes were found in other hematological parameters. Average HR during submaximal exercise significantly increased from sea level to day 2, however, no significant difference was found after day 12. La and RPE after submaximal exercise remained unchanged. Interestingly, the amount of changes (d) in supine HR from day 2 to 14 significantly correlated with dcortisol (from pre to day 8 & 14), daverage HR during cycling test and La after cycling test (from day 2 to 14). The amount of change in standing HR from day 2 to 14 significantly correlated with dEPO (from pre to 48 hours), dHb (from day 2 to day 8 & 14), and daverage HR during submaximal cycling test (from day 2 to 14), and dcortisol (from day 2 to 14). Conclusion: This study suggested that heart rate at supine and standing positions reflected physical condition and adaptation status to high altitude training in endurance athletes